2019
DOI: 10.1002/ardp.201900033
|View full text |Cite
|
Sign up to set email alerts
|

Potent ribonucleotide reductase inhibitors: Thiazole‐containing thiosemicarbazone derivatives

Abstract: The antioxidant, antimalarial, antibacterial, and antitumor activities of thiosemicarbazones have made this class of compounds important for medicinal chemists. In addition, thiosemicarbazones are among the most potent and well-known ribonucleotide reductase inhibitors. In this study, 24 new thiosemicarbazone derivatives were synthesized, and the structures and purity of the compounds were determined by IR, 1 H NMR, 13 C NMR, mass spectroscopy, and elemental analysis. The IC 50 values of these 24 compounds wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…6 Several studies have focused on the ability of pyridine compounds to bind to and inhibit the aromatase (CYP19A1) enzyme. [7][8][9] In a previous study reported by us on benzofuran derivatives, the aromatase inhibitory activity was found to be directly proportional to the heterocyclic nitrogen basicity (pKa: imidazole, 14.5; triazole, 10; pyridine, 5.2; tetrazole, 4.8), 6 however we also observed improved cytotoxicity profile (LC 50 /IC 50 >2000) of pyridine derivatives compared with triazole derivatives. We have recently reported potent low nanomolar/picomolar extended 4 th generation aromatase inhibitors based on a benzofuran-2-yl pharmacophore containing a triazole group as the azole required for haem binding.…”
Section: Introductionsupporting
confidence: 57%
“…6 Several studies have focused on the ability of pyridine compounds to bind to and inhibit the aromatase (CYP19A1) enzyme. [7][8][9] In a previous study reported by us on benzofuran derivatives, the aromatase inhibitory activity was found to be directly proportional to the heterocyclic nitrogen basicity (pKa: imidazole, 14.5; triazole, 10; pyridine, 5.2; tetrazole, 4.8), 6 however we also observed improved cytotoxicity profile (LC 50 /IC 50 >2000) of pyridine derivatives compared with triazole derivatives. We have recently reported potent low nanomolar/picomolar extended 4 th generation aromatase inhibitors based on a benzofuran-2-yl pharmacophore containing a triazole group as the azole required for haem binding.…”
Section: Introductionsupporting
confidence: 57%
“…Molecules are required to be between the Solute Dipole Moment of 1.0-12.5 Debye. Many other parameters are indicated as follows - Solute Total SASA: total solvent-accessible surface area; Solute Carbom Pi SASA: Van der Waals surface area of polar nitrogen and oxygen atoms and carbonyl carbon atoms; QPlogPo/w: Predicted octanol/water partition coefficient; QPlogS: Predicted aqueous solubility; log S: S in mol dm-3 is the concentration of the solute in a saturated solution that is in equilibrium with the crystalline solid; QPlogBB: brain/blood partition coefficient; QPlogKhsa: binding to human serum albumin; Apparent Caco-2 Permeability: Predicted apparent Caco-2 cell permeability (nm/s) where Caco-2 cells are a model for the gut–blood barrier; QP log BB for brain/blood: Predicted brain/blood partition coefficient for orally delivered drugs; Apparent MDCK Permeability: Predicted apparent MDCK cell permeability (nm/s) where MDCK cells are considered to be a good mimic for the blood-brain barrier; % Human Oral Absorption in Gl: Human oral absorption on a 0-100% scale (>80% is high, <25% is poor); Solute as Donor-Hydrogen Bonds: Predicted number of donor hydrogen bonds; Solute as Acceptor-Hydrogen: Predicted number of acceptor hydrogen bond; QP log p for X/Y: Predicted X/Y partition coefficient; IC50 value for the blockage of HERG K + channels (acceptable range: above 25.0); Solute CdW Polar SA (PSA): total polar surface area (Acar et al., 2019 ; Bicak et al., 2019; Budama-Kilinc et al., 2018; Ertas et al., 2019 ; Kecel-Gunduz et al., 2020; Menteşe et al., 2019 ; Mermer et al., 2019 ; Sari et al., 2019; Singh & Bast, 2014 ); Lipinski Rule of 5 Violations: Number of violations of Lipinski's rule of five where the rules are: mol_MW (molecular weight of the molecule) < 500; QPlogPo/w (predicted octanol/water partition coefficient) < 5; donorHB (hydrogen-bond donor atoms) ≤ 5; accptHB (hydrogen-bond acceptor atoms) ≤ 10 where compounds that provide these rules are considered as drug-like molecules (Saglık et al., 2019a; Saglık et al., 2019 b; Lipinski et al., 1997 ; Jorgensen & Duffy, 2002); and Jorgensen Rule of 3 Violations: Number of violations of Jorgensen's rule of three where the three rules are: QPlogS (predicted aqueous solubility) > −5.7, QPPCaco (predicted apparent Caco-2 cell permeability in nm/s) > 22 nm/s, # Primary Metabolites < 7 where compounds with fewer (and preferably no) violations of these rules are more likely to be orally available agents. When the numerical values of these parameters are very close to each other, as can be seen from Table 7 , it can be concluded that the results obtained show the potential future use of these three molecules as drugs, and will not cause a problem according to ADME analyses.…”
Section: Resultsmentioning
confidence: 99%
“…No:425-301, HIDEX, Finland) at the wavelength of 570 nm. Percent cytotoxicity and IC 50 values were calculated [22,23].…”
Section: Discussionmentioning
confidence: 99%